(untitled) (Global Journal of Human-Social Science, 2023)
Women have suffered various forms of violence for millennia. They are physical, mutilation, and moral violence in different environments. They were kept until the middle of the 20th century in private spaces, because public spaces were for men and for the practice of attitudes considered immoral for women. They were restricted in their freedom of movement and expression; they were used as a workforce when necessary to supplement the family income because, in some periods, the paid work done by women violated moral and religious precepts, whose symbol of sanctity was the Virgin Mary, a mirror of purification to be followed by women. Dealing with these aspects, the present article aims at substantiating whether the discrimination suffered by women in the labor market is based on historicalsociocultural, biological and/or legal factors, besides the distinction between sex and gender. In light of this analysis, a categorization is created that distinguishes the factors of discrimination. The deductive method was used and, as research techniques, a bibliographical survey was carried out on the theme under analysis.